2013
DOI: 10.3390/jfb4010038
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Human Microvascular Endothelial Cells on Topographical Substrates to Mimic the Human Corneal Endothelium

Abstract: Human corneal endothelial cells have a limited ability to replicate in vivo and in vitro. Allograft transplantation becomes necessary when an accident or trauma results in excessive cell loss. The reconstruction of the cornea endothelium using autologous cell sources is a promising alternative option for therapeutic or in vitro drug testing applications. The native corneal endothelium rests on the Descemet’s membrane, which has nanotopographies of fibers and pores. The use of synthetic topographies mimics the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…In this study we investigated, for the first time, the effects of EGFR‐TKIs on human dermal microvascular endothelial cells. As HMEC‐1s represent a unique immortalized human microvascular endothelial cell line that is useful in dissecting the role of the microvascular endothelium in pathophysiologic processes, HMEC‐1s are considered as an alternative cell source to overcome the limited lifespan of HMVECs . Our results demonstrated that endothelial cell proliferation was inhibited by the EGFR‐TKIs in a time‐dependent manner.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In this study we investigated, for the first time, the effects of EGFR‐TKIs on human dermal microvascular endothelial cells. As HMEC‐1s represent a unique immortalized human microvascular endothelial cell line that is useful in dissecting the role of the microvascular endothelium in pathophysiologic processes, HMEC‐1s are considered as an alternative cell source to overcome the limited lifespan of HMVECs . Our results demonstrated that endothelial cell proliferation was inhibited by the EGFR‐TKIs in a time‐dependent manner.…”
Section: Discussionmentioning
confidence: 61%
“…Since the pathologic events of purpuric drug eruptions take place at the level of the microvasculature, HMVECs (human dermal microvascular endothelial cells) would be useful in the dissection of the role of the microvascular endothelium in these pathologic processes . However, HMVECs have a low proliferative capacity and limited lifespan .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape factor of a perfect hexagonal cell (eg. a RPE cell) is around 0.9 [ 42 ]. The relationship between microglial cell number and the shape factor of the RPE was analyzed by linear regression using SPSS statistics software (IBM, Chicago, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The shape factor of a perfect hexagonal cell (eg. an RPE cell) is around 0.9 (43).The relationship between microglial cell number and the shape factor of the RPE was analyzed by linear regression using SPSS statistics software (IBM, Chicago, IL, USA).The quanti cation was con rmed by two independentresearchers.…”
Section: Retinal and Rpe/choroidal Atmount Preparation And Stainingmentioning
confidence: 99%